2022
DOI: 10.3390/ijms23063061
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc Protein Level Affected by Unsymmetrical Bisacridines Influences Apoptosis and Senescence Induced in HCT116 Colorectal and H460 Lung Cancer Cells

Abstract: Unsymmetrical bisacridines (UAs) are highly active antitumor compounds. They contain in their structure the drugs previously synthesized in our Department: C-1311 and C-1748. UAs exhibit different properties than their monomer components. They do not intercalate to dsDNA but stabilize the G-quadruplex structures, particularly those of the MYC and KRAS genes. Since MYC and KRAS are often mutated and constitutively expressed in cancer cells, they can be used as therapeutic targets. Herein, we investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
3
3
0
Order By: Relevance
“…On the other hand, our preliminary NMR studies have strongly suggested that both C-1311 and UAs exhibit well-defined interactions with several DNA G-quadruplexes, which are currently regarded as very attractive molecular targets in anticancer therapy. These findings are perfectly in line with our previous reports, which displayed that UAs inhibit the expression of K-Ras in Panc-1 cells 1 , as well as c-Myc in H460 cells 30 . Advanced NMR studies on the resulting G4/UA complexes and the implications of their formation will be discussed in our future work.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, our preliminary NMR studies have strongly suggested that both C-1311 and UAs exhibit well-defined interactions with several DNA G-quadruplexes, which are currently regarded as very attractive molecular targets in anticancer therapy. These findings are perfectly in line with our previous reports, which displayed that UAs inhibit the expression of K-Ras in Panc-1 cells 1 , as well as c-Myc in H460 cells 30 . Advanced NMR studies on the resulting G4/UA complexes and the implications of their formation will be discussed in our future work.…”
Section: Discussionsupporting
confidence: 93%
“…Recent experiments showed that C-2028 and other UAs exhibited well-defined interactions with several DNA G-quadruplexes, which are currently regarded as very attractive molecular targets in anticancer therapy [1]. This supported previous reports on the ability of UAs to inhibit the expression of K-Ras in Panc-1 pancreatic cancer cells [1] and c-Myc in HCT116 colorectal and H460 lung cancer cells [6]. The knowledge about the molecular background of UA action is constantly increasing.…”
Section: Introductionsupporting
confidence: 74%
“…These compounds exhibit high cytotoxic and antitumor activity against many human tumors, mainly those in the lung, colon, prostate, breast, and pancreas [24]. We thoroughly investigated the cellular effects of selected UAs on an HCT116 colon and H460 lung cancer cells, and we showed that these compounds induced apoptosis in the cells of both cell lines; moreover, the induced apoptosis occurred earlier and to a greater extent in H460 compared to HCT116, and this was confirmed by the morphological changes in the nuclei, the presence of a sub-G1 population, active caspase-3, and cleaved PARP along with the annexin V/PI staining and the analysis of the changes in the mitochondrial membrane potential [25]. We have also shown that a noncovalent attachment of UAs to quaternary quantum dots (QDs) improved their cytotoxic activity in lung cancer cells and had protective effects on normal cells [26].…”
Section: Introductionsupporting
confidence: 52%
“…It has been observed lately that the localization of UAs in cells is pH-dependent, and an increased concentration of these compounds in organelles with low pH has also been detected [25,51]. This-along with the fact that pH strongly influences UA protonation states, self-association ratio, and solubility [52]-may provide some insight into why some of these compounds exhibit even more promising results in 3D spheroids, which are characterized by a specific pH gradient that is similar to that observed in vivo.…”
Section: Discussionmentioning
confidence: 99%